PIRAEUS: A NEW CITY FOUNDED AT THE DAWN OF THE 19TH CENTURY, AROUND THE BIRTH OF THE GREEK STATE - Moira, Maria (Design/Arts/Culture, 2022)
Book review of Nikos Belavilas, History of the City of Piraeus. 19th and 20th century (in Greek), Alexandria Publications, Athens 2021, 599 pages. Piraeus is a charming seaside city, bustling and vibrant, filled with contradictions; a Mediterranean seaport of regional importance, with geophysical singularities and an extensive lace-like coastline; a major cultural and social urban hub of national importance, which played an instrumental role in the industrialization and economic growth of Greece. Piraeus was a newly-founded city that was designed and situated by the sea, in order to serve the maritime transportations of the newly established state. Piraeus developed around the core of the deep bay formed by the Piraeus peninsula, on the site of the ruined ancient settlement and around the humble medieval port facilities, which framed this natural anchorage, in a location that would offer the new Athenian capital the necessary sea link and the infrastructure required for the development of its maritime and commercial activities.In this thoroughly engaging book, both in terms of methodological composition but also as a reading experience, Nikos Belavilas retrieves from an interdisciplinary domain and offers the main axes along which the narrative evolves: the city, the port and the industry. Around them revolves the history of the rapid strategic residential development of Piraeus.